2021
DOI: 10.21037/atm-21-6102
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter single-arm trial of sintilimab in combination with chemotherapy for neoadjuvant treatment of resectable esophageal cancer (SIN-ICE study)

Abstract: Background: Preoperative chemotherapy or chemoradiotherapy is the standard treatment for resectable esophageal cancer (EC); however, it is associated with increased postoperative complications and mortality.Recently, Immune Checkpoint inhibitors have been incorporated in the treatment of advanced EC. Its role in the preoperative setting has not been established yet. In this multicenter, single-arm study, we evaluated the efficacy and safety of neoadjuvant therapy with sintilimab in combination with chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 18 publications
0
57
0
Order By: Relevance
“…Furthermore, in a recent retrospective study that performed two cycles of combination of chemotherapy and immunotherapy in neoadjuvant settings of ESCC, their results revealed a pCR of 22.2% to 35.3%, lower than the pCR in our study. It’s supposed that the cycles of neoadjuvant treatment may affect the efficacy, which deserves further studies to be confirmed ( 15 , 16 ). Moreover, pCR and MPR are verified to confer a survival advantage and to prolong median disease-free survival (DFS) in EC and many other cancers ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a recent retrospective study that performed two cycles of combination of chemotherapy and immunotherapy in neoadjuvant settings of ESCC, their results revealed a pCR of 22.2% to 35.3%, lower than the pCR in our study. It’s supposed that the cycles of neoadjuvant treatment may affect the efficacy, which deserves further studies to be confirmed ( 15 , 16 ). Moreover, pCR and MPR are verified to confer a survival advantage and to prolong median disease-free survival (DFS) in EC and many other cancers ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…The selection process and reasons for study exclusion are shown in Figure 1. Among the 27 studies, 8 trials with 221 patients examined nICRT (14-21), 19 trials with 588 patients examined nICT (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Except one twoarms trial (33), all included studies were single-arm trials.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…(1) According to the Stooler classification [9,10], the degree of oesophageal stricture was grade II-VI. (2) The diameter of the oesophageal cavity was more than 2.6 mm, so an ultrasonic endoscope could pass.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…The patients were followed up between three to six months: (1) The symptoms would be consultated once a week through the cell phone.We would record the complication (perforation, bleeding, and infection), and degree of the dysphagia of oesophageal stricture [9]. (2) The endoscopy would be performed every three months after treatment.…”
Section: Follow-upmentioning
confidence: 99%
See 1 more Smart Citation